Social Media Engagement and Product Quality as Drivers of Purchase Intention in Sustainable Thrift Shopping - Husni Shabri; Fajar Ramadhan (MABIS Jurnal Manajemen Bisnis Syariah, 2025)
This study aims to analyze the influence of social customer engagement and product quality on consumer purchase intention in thrift stores. The research was conducted using a quantitative approach by distributing questionnaires to 97 consumers of Uncu Thriffting Store in Padang Panjang. Data were analyzed using multiple linear regression with SPSS version 27. The results indicate that social customer engagement and product quality have a positive and significant effect on consumer purchase intention, both partially and simultaneously. The coefficient of determination (R²) value of 72.1% shows that the two independent variables can explain the variation in purchase intention, while 27.9% is influenced by other factors outside the study. The practical implication of this research is the importance of consistency in digital interaction and maintaining product quality to increase consumer purchase intention in thrifting businesses.